Hospitalization admission rates for low-income subjects with full health insurance coverage in France - Tuppin, Philippe; Drouin, Jérôme; Mazza, Mohamed; Weill, Alain; Ricordeau, Philippe; Allemand, Hubert (European journal of public health, 2011)
Background: Complementary Universal Health insurance (CMUC) providing free access to health care has been available in France, since 2000 for people with an annual income <50% of the poverty threshold. Methods: Data were derived from the French national health insurance reimbursements and short-stay admissions database for 2007 (80% of subjects under the age of 60 years in France, including 4.8 million CMUC beneficiaries). Rate ratios were calculated by dividing the rate of CMUC beneficiaries by that of other beneficiaries standardized for the sex and age distribution of CMUC beneficiaries. Results: The hospitalization rate of CMUC beneficiaries was 17.2% and the standardized rate for non-CMUC beneficiaries was 13.2% (ratio: 1.3). It was equally raised regardless of gender and age of CMUC beneficiaries. The hospital mortality rate was 0.61% for CMUC beneficiaries and the adjusted rate for non-CMUC beneficiaries was 0.35% (1.8). The hospitalization ratio for CMUC beneficiaries was >1 for all of the 22 major diagnostic categories, including psychiatry, toxicology and alcohol (3.7), HIV (3.3), infectious diseases other than HIV (1.9), burns (2.6), trauma (1.7) and female genital tract tumours (1.6) but not breast tumours (0.8). Hospitalizations for investigations such as endoscopies were also more frequent, as well as stays of <48 h for radiotherapy (1.6), chemotherapy (1.5) and dialysis (2.2). Conclusions: In this low-income population with free access to health care, hospitalization and hospital mortality rates were higher for many diseases that are known targets for prevention and screening actions.